Improving efficiency of virgin coconut oil through process optimization in developing sustainable models for small scale production - Kamalasundari, S; Babu, R; ArunKumar, R; Shanthi, K; Jayaramachandran, M (Plant Science Today, 2025)
Virgin coconut oil (VCO) “healthiest oil in the world”, extracted from matured coconut kernel. The quality and quantity of VCO extraction is a major step in commercializing the product. If the process of VCO is made simple, coconut farmers will be able to reap the benefits. In this study, VCO production methods were optimized for micro and village scale processing that meets the international and domestic standards. Eight coconut varieties of Tamil Nadu Agricultural University were studied for VCO production using four processing methods viz., Traditional boiling method (T1- WM-TB), Modern Kitchen method (T2- WM-MK), Solar drying method (T3- DM-SD) and Cabinet drying method (T4- DM-CD). Advantages and disadvantages of all the four methods were analyzed and the yield and cost economics and limitations in each processing methods were discussed. The highest yield was given by DM-CD (41.43 %) DM-SD (40.89 %), WM-MK (20.32 %) and WM-TB (8.8 %). Physio-chemical analysis and quality characteristics were checked and found that sixteen compounds were commonly present in more than 95 % of the VCO samples. The results revealed that except for moisture all the physicochemical parameters as specified by APCC standards (15 parameters out of 16 parameters) and as per FSSAI standards (8 parameters out of 9 parameters) were in the specified range. From this study it is concluded that most of the quality parameters can be easily met by following good manufacturing practices of VCO and it can be produced at home-scale which will directly increase the income of the coconut farmers.